Review of the genus Arboridia Zachvatkin (Hemiptera: Cicadellidae: Typhlocybinae), with description of two new species from China - Song, Yue-Hua; Li, Zi-Zhong (Zootaxa, 2015)
The genus Arboridia Zachvatkin is reviewed, including two new species Arboridia cincta sp.nov. and Arboridia ochracea sp.nov., from Henan province, China. A detailed morphological description and illustrations of the two new species are provided. A key to all known species from China is given.